Pengaruh Fasilitas, Kualitas Pelayanan, dan Kualitas Produk terhadap Kepuasan Pasien di Puskesmas Kapongan Situbondo - Achmad Shodiq; Dassucik Dassucik; Ahmad Hafas Rasyidi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the influence of product uniqueness, promotion, and price on contemporary beverage purchase decisions. The research approach used is a quantitative approach with the type of explanatory research. The sampling technique used non-probability sampling using the purposive sampling method, with a sample of 100 respondents who were contemporary beverage consumers. The data collection method was carried out through the distribution of questionnaires measured using the Likert scale, while data processing and analysis were carried out using the SPSS application. The results of the study showed that based on the determination coefficient test, the R Square value was obtained of 0.468. This shows that the variables of product uniqueness, promotion, and price were able to explain the variation in purchase decisions by 46.8%, while the remaining 53.2% were influenced by other variables that were not included in the research model, such as brand image, business location, and service quality. These findings indicate that marketing strategies that emphasize product innovation, attractive promotions, and pricing that are in line with consumers' purchasing power have an important role in improving purchasing decisions. The results of this research are expected to be considered for business actors in developing more effective and competitive marketing strategies.